The Impact of Oil Price Fluctuations on Development of Iraqi Economy - Jassim Al-Yasiri, Ahmed; Qais Abbas, Zainab (International Journal of Psychosocial Rehabilitation, 2020)
Since the discovery of oil and the use of technology in industries, oil has become the main source of energy for the major industrialized countries, meaning that it has become the source of the effective power of the producing countries. Oil in Iraq is the source of economic strength. However, this source requires intervention to exploit and use it, and to a legal and legislative framework that regulates the process of investing this resource. It is managed by an international market, one of the largest markets that is characterized by high export and import volume because it is produced in specific countries and is widely used in other countries. This market is distinguished from other markets by its volatile and variable prices due to factors related to market fundamentals in terms of demand and supply and the rate of economic growth. The Iraqi economy relies heavily on the oil sector to finance its revenues. Therefore, rentier economies will be affected in the case of lower prices because the rates of economic growth and government spending depend on the production and export of crude oil. Therefore, a strategy must be devised to develop this resource and make good use of its proceeds.